Allograft function predicts mortality in kidney transplant recipients with severe COVID-19: a paradoxical risk factor - Luo, Han; Wen, Jingyu; Yang, Hongji; Ran, Qing; Hou, Yifu (Frontiers in Immunology, 2024)
Introduction Kidney transplant recipients (KTRs) are at a higher risk of severe coronavirus disease (COVID-19) because of their immunocompromised status. However, the effect of allograft function on the prognosis of severe COVID-19 in KTRs is unclear. In this study, we aimed to analyze the correlation between pre-infection allograft function and the prognosis of severe COVID-19 in KTRs. Methods This retrospective cohort study included 82 patients who underwent kidney transplantation at the Sichuan Provincial Peoples Hospital between October 1, 2014 and December 1, 2022 and were diagnosed with severe COVID-19. The patients were divided into decreased eGFR and normal eGFR groups based on the allograft function before COVID-19 diagnosis (n=32 [decreased eGFR group], mean age: 43.00 years; n=50 [normal eGFR group, mean age: 41.88 years). We performed logistic regression analysis to identify risk factors for death in patients with severe COVID-19. The nomogram was used to visualize the logistic regression model results. Results The mortality rate of KTRs with pre-infection allograft function insufficiency in the decreased eGFR group was significantly higher than that of KTRs in the normal eGFR group (31.25% [10/32] vs. 8.00% [4/50], P=0.006). Pre-infection allograft function insufficiency (OR=6.96, 95% CI: 1.4633.18, P=0.015) and maintenance of a mycophenolic acid dose >1500 mg/day before infection (OR=7.59, 95% CI: 1.0853.20, P=0.041) were independent risk factors, and the use of nirmatrelvir/ritonavir before severe COVID-19 (OR=0.15, 95% CI: 0.030.72, P=0.018) was a protective factor against death in severe COVID-19. Conclusions Pre-infection allograft function is a good predictor of death in patients with severe COVID-19. Allograft function was improved after treatment for severe COVID-19, which was not observed in patients with non-severe COVID-19.